Local Government Efforts to Implement Government Policies in Improving the Quality of Islamic Education in Mandailing Natal District - Lubis, Siti Hawa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
One of the educational problems faced by the Indonesian people is the low quality of education at every level and unit of education, especially primary and secondary education. In fact, government policies to improve the quality of educational institutions are carried out in various ways. This study aims to obtain a complete picture of the implementation of local government policies in improving the quality of Islamic education in Mandailing Natal Regency with a qualitative approach. The implementation of policies in Mandaling Natal Regency is that policies are formulated into certain action programs and projects that are designed and financed. The program is implemented according to plan. policy Policies or programs are broadly influenced by the content of the policy and the context of its implementation. The whole policy is evaluated by measuring the level of success of the program based on the policy objectives. Policy is seen through its impact on the intended targets, both individuals and groups as well as society.